An evaluation of popular search engines on finding turkish documents - Demirci, Rabia Gülçin; Kismir, Vildan; Bitirim, Yıltan (My University, 2007)
This article investigates the information retrieval performance of popular search engines on finding Turkish documents. First of all, five popular search engines (Google, Yahoo, Msn, AlltheWeb and Ask) and a list of Turkish queries are determined. Each query is run on each search engine one by one and first twenty documents on each retrieval output are evaluated as being 'relevant' and 'non-relevant'. Then, for evaluation of search engines precision and normalized recall ratios are calculated at various cut-off points for each query and search engine. Furthermore, the results are used to make comparison of the search engines with local search engines. Overall, Google appears to be the best search engine in terms of average precision (73%) and normalized recall ratios (66%), on finding Turkish documents. However, local search engines have lower information retrieval performance to finding Turkish documents and need more improvement than international search engines. © 2007 IEEE.
2nd International Conference on Internet and Web Applications and Services, ICIW'07 --
Keywords: Information retrieval; Information retrieval systems; Query processing; World Wide Web; Cut-off points; Google; Normalized recall ratios; Retrieval output; Search engines